Restoring hearing and balance in a mouse model of slc26a4 - related deafness - Li, Xiangming (Kansas State University, 2013)
Mutations of SLC26A4 are the most common cause of the hearing loss associated with enlargement of the vestibular aqueduct. SLC26A4 encodes pendrin, an anion exchanger expressed in the cochlea, the vestibular labyrinth, and the endolymphatic sac of the inner ear. Slc26a4Δ/Δ mice, devoid of pendrin expression, develop an enlarged membranous labyrinth which leads to the failure to develop hearing, thereby recapitulating the human disease. Identifying the ionic composition of the endolymph and evaluating the importance of pendrin expression at various sites are initial steps towards developing strategies for preventing enlargement of the endolymph volume and subsequently restoring the inner ear functions. The major aims of the present study are 1) To determine the ionic composition of inner ear fluids during the developmental phase in which the enlargement of the endolymph volume occurs; 2) To test the hypothesis that pendrin expression in the endolymphatic sac is more important than its expression in the cochlea and the vestibular labyrinth. Here, we determined the Na+ and K⁺ concentrations in the cochlea and the endolymphatic sac with double-barreled ion-selective electrodes and generated a mouse model that restores pendrin expression in the endolymphatic sac while lacking expression in the cochlea and the vestibular labyrinth. High Na⁺ and low K⁺ concentrations were found in the cochlear endolymph during the embryonic stage. A rise of the K⁺ concentration along with a decline of the Na⁺ concentration occurred shortly before birth. The site-specific restoration of pendrin to the endolymphatic sac prevented enlargement and rescued hearing and balance. In conclusion, these data demonstrate that endolymph, in the phase of luminal enlargement during the embryonic development, is a Na⁺-rich fluid that is modified into a K⁺-rich fluid just before birth; restoration of pendrin in the endolymphatic sac is sufficient for developing normal inner ear function. Furthermore, these data suggest enlargement of endolymph volume caused by the loss of Slc26a4 is a consequence of disrupted Na⁺ absorption. Moreover, pharmacological strategies that correct fluid transport, as well as spatially and temporally limited restorations of pendrin, might restore normal inner ear functions in humans carrying mutations of SLC26A4.
Keywords: Enlarged vestibular aqueduct; Inner ear; EndolymphPendrin; Biochemistry (0487)